Impact of Brand Image, Brand Affect, Brand Trust on Customer Brand Extension Attitude: The Mediating Role of Brand Loyalty - Jayasekara, D.; Perera, C. (NSBM Green University, 2021)
Manufacturing companies operate in a strong competitive environment due to the homogenous nature of their marketing activities and always look for new marketing strategies to be competitive in the marketplace. Fierce competition forces the manufacturing companies to get a competitive advantage over the competitor to remain in the market and gain a higher market share. Therefore, brand extension has become crucial to differentiate themselves from others to attract prospective customers. Despite many benefits achieved by implementing successful brand extension strategies, several obstacles negatively influence both the extended brand and the parent brand. Although the literature has recognized the role of brand extension in general product purchase, little is known about how products with different brand images, brand affect, and brand trust affect brand extension from the perspectives of the customers. Further, a dearth of literature remains on the mediating effect of brand loyalty towards the brand extension attitudes of the customers.Accordingly, the main objective of this study is to examine the extent to which brand image, brand affect, and brand trust influence the customer brand extension attitude in the manufacturing sector in Sri Lanka. The present study considers the mediating effect of brand loyalty in developing the relationship between the study constructs.For this study, descriptive and inferential statistical analyses were employed to show the associations and predictive abilities of the independent variables within each construct. Statistical Package for Social Sciences (SPSS) version 21 was used to analyze the quantitative data.The quantitative findings from 200 customers indicated that brand image, brand affect, and brand trust develop brand extension attitudes among the customers. Brand loyalty was found to mediate the effect on customer brand extension attitude. The findings of this study enrich the marketing literature and have implications for manufacturing companies in developing customers’ attitudes through a variety of branding strategies
Keywords: Impact of Brand Image; Brand Affect; Brand Trust on Customer Brand Extension Attitude: The Mediating Role of Brand Loyalty